Efeito do comprimento de onda e da intensidade da luz sobre o ritmo circadiano de atividade motora em saguis (Callithrix jacchus) - Dias, Rosane Maria Simon Lampert (2016)
Circadian entrainment depends on a complex interaction between light information and photoreceptor cells. The neurobehavioral circadian light effects are mediated primarily by retinal ganglion cells. Rods and cones operate in light detection and also interfere in the circadian timing system, but the mode of action of these photoreceptors in the control of circadian rhythms in diurnal non-human primates is unknown. Our study evaluated the effect of wavelength and intensity of light on parameters of the circadian activity rhythm in marmosets by analyzing the effect of short and long wavelengths of light in three light intensities. The locomotor activity was monitored by infrared sensors in 16 adult male marmosets, kept in controlled temperature and humidity in a light/dark (LD) cycle 12:12. The effect of two wavelengths in light phase were evaluated: short, with λmax 463 nm - in the spectral region of blue light, and long: with λmax 631 nm - in the spectral region of red light, in three light intensities: 200, 100 and 10 lux, in relation to control condition (fluorescent light). At the end of each stage, the marmosets were maintained in constant light (LL) under 10 lux and 200, to analyze the mechanisms of synchronization. An interval lasting 15 days (fluorescent light - 200 lux/2 lux) was given between the stages with different wavelengths. During the exposure to blue and red lights, the phase angle of the end of active phase was anticipated, and the duration of the active phase and the total daily activity were lower in relation to the control condition, with modulations at 10 lux. There was an increase in the spectral power of circadian period in blue and red lights in LL under 200 lux. We also observed that the duration of the experiment modifies the expression of circadian activity rhythm, possibly affecting the photoreception mechanisms in marmosets. From these results it is suggested that: 1) blue and red wavelengths of light used in LD cycles modify the endogenous expression and photic synchronization of the circadian activity rhythm in marmosets; 2) the animals respond differently to blue and red wavelengths of light at the beginning and end of active phase, with a larger advance the end of active phase, reducing the length of alpha and total daily activity, probably due to a masking effect; 3) the effect of wavelength varies depending on light intensity, with no difference between the intensities of 200 and 100 lux and a greater instability at 10 lux; 4) the duration of exposure of animals to blue and red wavelengths is a factor to be considered in the construction of experimental protocols with this species.